2017
DOI: 10.1161/jaha.116.004869
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Gradient Within Coronary Sinus Predicts the Long‐Term Outcome of Persistent Atrial Fibrillation Catheter Ablation

Abstract: BackgroundThe coronary sinus (CS), as a junction of the atria, contributes to atrial fibrillation (AF) by developing unstable reentry, and isolating the atria by ablation at the CS could terminate AF. The present study evaluated whether AF activities at the CS in a subset of patients contributed to AF maintenance and predicted clinical outcome of ablation.Methods and ResultsWe studied 122 consecutive patients who had a first‐time radiofrequency ablation for persistent AF. Bipolar electrograms were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…While there have been several applications of frequency domain analysis and morphology RQA techniques in the setting of catheter ablation of AF, to the best of our knowledge, there has been no study to date that has shown changes in EGMs as a result of directed rotor ablation (outside of conventional pulmonary vein isolation). Previous studies have suggested the role of DF, OI, and RQA in the prediction of short‐ and long‐term outcomes in AF ablation. Several other studies have also suggested that both OI and morphology RQA may describe foci of atrial organization critical to the maintenance of AF.…”
Section: Discussionsupporting
confidence: 90%
“…While there have been several applications of frequency domain analysis and morphology RQA techniques in the setting of catheter ablation of AF, to the best of our knowledge, there has been no study to date that has shown changes in EGMs as a result of directed rotor ablation (outside of conventional pulmonary vein isolation). Previous studies have suggested the role of DF, OI, and RQA in the prediction of short‐ and long‐term outcomes in AF ablation. Several other studies have also suggested that both OI and morphology RQA may describe foci of atrial organization critical to the maintenance of AF.…”
Section: Discussionsupporting
confidence: 90%
“…Pulmonary vein isolation (PVI) is the cornerstone of catheter ablation for atrial fibrillation (AF) [ 1 , 2 ]. Avoiding gaps of the PVI circle is of great importance for effect of ablation.…”
Section: Introductionmentioning
confidence: 99%
“…On one side, ablation of the CS muscular sleeves with abolition of all electrical potentials eliminates an important source of rapid repetitive electrical activity that may be involved in AF initiation. 12,13 On the other side, CS isolation may interrupt an important electrical connection between the atria and avoid the development of unstable re-entry, thereby preventing AF perpetuation. 14,15 In a series of 45 paroxysmal and persistent AF patients, 14 RFCA targeting the CS led to significant prolongation of the fibrillatory cycle length and terminated AF in approximately 35%.…”
Section: Discussionmentioning
confidence: 99%